Optimization of Intelligent Distribution of Distribution Network in the Presence of Distributed Sources. (26th September 2022) - Song, Youle; Nie, Ding; Fan, Litao
Abstract : In order to improve the intelligent distribution effect of the distribution network in the presence of distributed generation, this study combines intelligent algorithms to analyze the intelligent distribution of the distribution network in the presence of distributed generation. Moreover, this study establishes an objective function composed of system network loss expectation, voltage stability index, and reactive power compensation equipment investment. In addition, this study improves the artificial bee colony algorithm through tabu search algorithm and genetic algorithm and obtains an improved TS-IABC algorithm. Finally, this study compares and tests the performance of different algorithms in the form of functions and simulations. The simulation results show that the optimal intelligent distribution method of the distribution network in the presence of distributed power generation proposed in this study has a good effect and can promote the intelligent distribution of the distribution network.